Mechanism of Human Tooth Eruption: Review Article Including a New Theory for Future Studies on the Eruption Process - Inger Kjær (Scientifica)
Human eruption is a unique developmental process in the organism. The aetiology or the mechanism behind eruption has never been fully understood and the scientific literature in the field is extremely sparse. Human and animal tissues provide different possibilities for eruption analyses, briefly discussed in the introduction. Human studies, mainly clinical and radiological, have focused on normal eruption and gender differences. Why a tooth begins eruption and what enables it to move eruptively and later to end these eruptive movements is not known. Pathological eruption courses contribute to insight into the aetiology behind eruption. A new theory on the eruption mechanism is presented. Accordingly, the mechanism of eruption depends on the correlation between space in the eruption course, created by the crown follicle, eruption pressure triggered by innervation in the apical root membrane, and the ability of the periodontal ligament to adapt to eruptive movements. Animal studies and studies on normal and pathological eruption in humans can support and explain different aspects in the new theory. The eruption mechanism still needs elucidation and the paper recommends that future research on eruption keeps this new theory in mind. Understanding the aetiology of the eruption process is necessary for treating deviant eruption courses.